1995
DOI: 10.3109/01913129509021910
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Cervical Lymphadenopathy Due to Ki-1 Lymphoma in an Elderly Female

Abstract: A 70-year-old female presented with recurring cervical lymphadenopathy over a 5-year period. Intermittently, symptoms of respiratory and GI tract disease occurred, raising the possibility of malignancy. Investigation of these systems and of the breasts were negative. A lymph node biopsy was eventually done and showed intrasinusoidal proliferations of CD30-positive malignant cells which were also characterized ultrastructurally. Therapy with CHOP has produced a good initial response. The value of electron micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2002
2002

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…This is a high-grade malignant lymphomawith morphologic features of large cells, including a Reed-Sternberg-like cell appearance, and the expression of the Ki-1 (CD30) antigen or epithelial membrane antigen (EMA) (1 , 2). Although it has been reported that primary ALCLof the skin may undergo spontaneous regression (3)(4)(5), there is only one report in which ALCL without cutaneous involvement showedspontaneous regression oflymphadenopathy (6). The present report describes a 44-year-old man with a Ki-1 (CD30)-positive ALCLaccompanied by spontaneously regressing lymphadenopathy.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…This is a high-grade malignant lymphomawith morphologic features of large cells, including a Reed-Sternberg-like cell appearance, and the expression of the Ki-1 (CD30) antigen or epithelial membrane antigen (EMA) (1 , 2). Although it has been reported that primary ALCLof the skin may undergo spontaneous regression (3)(4)(5), there is only one report in which ALCL without cutaneous involvement showedspontaneous regression oflymphadenopathy (6). The present report describes a 44-year-old man with a Ki-1 (CD30)-positive ALCLaccompanied by spontaneously regressing lymphadenopathy.…”
Section: Introductionmentioning
confidence: 74%
“…Although transbronchial lung biopsy was of no diagnostic value due to the smallness of the lung nodules, we suspected that the pulmonary lesions indicated involvement of ALCLbecause they also improved with spontaneous improvement of the lymphadenopathy. It has been reported that primary ALCLof the skin may undergo spontaneous regression (3)(4)(5), however there has only been one report (6) in which ALCLwithout cutaneous involvement showed spontaneous regression of lymphadenopathy.…”
Section: Discussionmentioning
confidence: 99%